Digital Exposure and Adolescent Mental Health: Implications for Educational Settings - Waldimer Pasaribu; Dessy Pramudiani; Ferdinan Leonadus Lopo (Jurnal Ragam Pengabdian, 2026)
This study investigates the impact of digital media exposure on adolescent mental health, particularly within educational settings. With increasing screen time among adolescents, concerns about mental health issues like anxiety, depression, and social isolation have risen. The research aims to explore the relationship between digital exposure and mental well-being, focusing on how it affects academic performance and social development. A library-based methodology was employed, using secondary data from books, journals, and previous studies. The findings reveal a strong correlation between excessive digital media use and mental health challenges, particularly anxiety and depression, while also highlighting the role of schools in mitigating these effects. The study concludes that educational institutions should implement digital literacy programs and set guidelines to manage digital distractions, fostering a balanced use of technology for better mental health and academic outcomes. Further research is needed to explore long-term effects and diverse socio-economic contexts.